Development of electronic textiles to support networks, communications, and medical applications in future U.S. Military protective clothing systems. - Winterhalter, C.A.
The focus of this paper is on the development of textile-based wearable electronics that can be integrated into military protective clothing. A materials and manufacturing survey was conducted to determine the best performing and most durable materials to withstand the rigors of textile manufacturing and potential military use. Narrow woven technology was selected as one of the most promising textile manufacturing methods. A working wearable narrow fabric version of the Universal Serial Bus (USB), as well as a radiating conductor, were successfully developed and fabricated. A circular knit T-shirt with an integrated spiral bus was also developed. Military products developed include components of a personal area network providing data and power transport, and a body-borne antenna integrated into a load-bearing vest.
Keywords: Body-borne antenna; Circular knit T-shirt.; Communication network; Data transport; Integrated spiral bus; Load-bearing vest; Medical applications; Military protective clothing system; Narrow woven technology; Personal area network; Power transport; Radiating conductor; Soldier; Textile manufacturing; Textile-based wearable electronics development; Universal serial bus; Wearable narrow fabric version